SUBAK SEBAGAI PARIWISATA BUDAYA DENGAN KONSEP TRI HITA KARANA - IG Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Bali develops Subak as a Cultural Tour, because culture is the most potential for people’s lives in bali. The basic capital of cultural tourism is the culture of normative and operational functions. As a cultural normative role is expected to be able and potential in providing identity, basic handling, controlling pattern, so that the balance and culture ketahana also expected to be the main attraction for the increase of tourism. It gives a clue how important the role of culture in tourism development. So it does not mean culture for tourism but otherwise tourism for culture. Subak for the Balinese is not just an irrigation system, but also a life philosophy for the Balinese themselves. In view of the Balinese, Subak is a direct reflection of the Hindu philosophy of Tri Hita Karana (the three causes of goodness), which encourages harmonious relationships between individuals and souls (parahyangan), human (pawongan), and nature (palemahan). As a system of living together, Subak can survive for a century more because people are loyal to the ancestral tradition. Water distribution is done fairly, all issues are discussed together, even up to the time of planting and the type of rice. Sanctions against all forms of offenses will be determined by the residents themselves through a ceremony performed at the temple. Harmonization of life is the key to preserving Subak culture.Keywords: Subak, Cultural Tourism, Tri Hita Karana